Análisis de Errores Semánticos por la Interferencia de la LM y LE1 en la Producción Escrita de los Aprendices Iraquíes de ELE - قــيس إبـراهــيم غــيداء (Al-Adab Journal, 2018)
The Interference and Transition Errors in the Fild of Semantic Resulting from First and Second Language in The Writing Production of Iraqi Apprentices when Teaching Spanish as a Foreign Language The acquisition of a foreign language for students can not be crossed only with the help of a. Here, the student begins to strengthen his tools of the rules and vocabulary (semantic, cultural), stages enhances the linguistic and communicative abilities, and the role of a professor in the field of foreign language learning is to help the student to overcome the difficult stages and prevent the commission of linguistic errors, for example, the negative interference of the mother language or any second language , the learner acquired during the various stages of study. To overcome such mistakes so we must - the task of the professor- identify strategies used by the student while speaking, writing when learning a foreign language with the knowledge of its causes, and so we can find ways to identify them with the correct teaching aids. Recently, it appeared the subject aroused the interest of many researchers in the field of foreign language learning, and that is the subject of "Analysis Errors", this new interest fields transforming the concept of error of old and traditional concept and put it in the new evaluation, as it is currently considered one of the essential tools in modern teaching methods when teaching a foreign language. So we all know that any foreign language education methods, in all stages, full of challenges and obstacles to the professor and to the student too. So this investigation is the my summary of continued and direct remarks with the Iraqi learner the Faculty of Languages in Baghda. It was highlighted in our research on the extraction of the following: The negative interference and transition errors in the semantic field, committed by the iraqi university student when he learned Spanish as a foreign language. And what causes it? And how to avoid them in the future? The study cited many examples extracted from three different stages of learning (intermediate and advanced) from the texts of Iraqi students in the Department of Spanish language / Faculty of Languages in Baghdad for two academic years, the interest of which is to know what the wrong strategies practiced by the learner in written tests - in the advanced stages of learning Spanish language - and identify the most important errors and concluded the results of research and recommendations that will contribute to the provision of the problems of the study solutions.